Generation of nano- and micro-sized organic pollutant emulsions in simulated road runoff. (December 2019) - Markiewicz, Anna; Strömvall, Ann-Margret; Björklund, Karin; Eriksson, Eva
Abstract: A wide range of organic pollutants (OPs) are emitted from the road and traffic environment and transported with road runoff to receiving waters. To provide an understanding of the transport routes of OPs in the environment, an investigation was carried out with the aim to determine whether OPs are transported with nano- and microparticles in the form of emulsions. Tests were performed on simulated road runoff, using laboratory prepared mixtures of ultrapure water and specific polycyclic aromatic hydrocarbons (PAHs), alkylphenols (APs) and their ethoxylates (APEOs), phthalates, diesel oil (aliphatic hydrocarbons), with and without addition of humic acid (HA) and iron (Fe) colloids. The samples were analysed directly after mixing and after a few days of stabilisation for particle size distribution (PSD) and concentrations of particles in the size range 10 nm–100 μm, and zeta potential > ± 500 mV. Further, after long-term storage to achieve stabilisation, selected samples were investigated for the PSD and particle concentrations in the ranges 10 nm–2 μm, to determine whether stable emulsions had formed. The following simulation mixtures, both mixed and stabilised, were identified as potential emulsions: diesel, APs and APEOs, diesel with APs and APEOS, phthalates, and a mixture of all OPs with and without colloids. Measurements with the Zetasizer and Nanosight instruments imply that the majority of particles in the samples were found in the nano-range of 30–660 nm respectively, and a smaller portion of particles < 28% also measured with Coulter Counter were found to be micro-sized. Higher concentrations of the smallest nanoparticles were found in the mixture of all OPs without colloids added, than in the OP mixture with colloids added. The results indicate that the addition of colloids favours the formation of larger micro-sized emulsions that may break down with time into nano-sized particles. In the mixed samples, the number of micro-sized particles decreased, while the number of nanoparticles increased; this process may also occur in road runoff transportation systems during heavy rain events. This is the first study to indicate that emulsions of OPs may be formed in road runoff, and that emulsions may act as carriers of OPs in urban stormwater. Graphical abstract: Unlabelled Image Highlights: Generation of emulsions in stormwater using solutions of OPs, diesel and colloids (83) Emulsions in micro- and nano-size can be produced in stormwater in presensce of OPs (84) Majority of particles occurred in the range 30–660 nm (55) Mixing reduces number of particles in micro-scale in samples with OPs and colloids (84) Long-term stabilisation increases number of particles in nanoscale (68)